A comparison between selenium dioxide and selenium methionine induced cytotoxicity in estrogen receptor negative and positive breast cancer cell lines - Kuppusamy, U.R.; Wan, Y.P.; Kanthimathi, M.S. (2005)
Selenium is an essential trace element which has been shown to inhibit the growth of various cancers in numerous studies. Different forms of selenium have been reported to exert variable potencies against the cancer growth. In this study, the effect of selenium dioxide (SeO ) and organic selenium (seleno-L-methionine) 2 on the growth of the human breast cancer cell lines namely MCF-7 (estrogen receptor positive) and MDA-MB-231 (estrogen receptor negative) were compared. The standard MTT (3-4,5-Dimethylthiazol-2-yl-2,5-diphenyltetrazolium bromide) assay was used to quantitate the viable cancer cells. Selenium dioxide inhibited cell growth at high concentrations (10G M to 10G M) but showed mild (not significant) stimulation of cell 4 3 proliferation at lower concentration (10G to 10G M). However, selenomethionine exhibited biphasic effects 12 5 on both cell lines. It inhibited cell growth at high concentrations (10G M to 10G M in MCF-7; 10G M in MDA-4 3 3 MB-231) but stimulated cell proliferation at lower concentrations. The findings in this study indicated that selenium dioxide was more potent than selenomethionine in inhibiting both cancer cell lines. Besides, both forms of selenium were also found to be less effective against MDA-MB-231.